163k views
2 votes
In the image below, m2OMN = (2x+9) and m2 LMN = (6x-7) and m2 OML = 66.
Find m ZOMN and m LMN

In the image below, m2OMN = (2x+9) and m2 LMN = (6x-7) and m2 OML = 66. Find m ZOMN-example-1
User Shilaghae
by
5.1k points

1 Answer

1 vote

Answer:

m<OMN = 25

m<LMN = 41

Explanation:

m<OMN = 2x + 9

m<LMN = 6x - 7

m<OML = 66

m<OMN + m<LMN = m<OML

2x + 9 + 6x - 7 = 66

8x + 2 = 66

8x = 64

x = 8

m<OMN = 2x + 9 = 2(8) + 9 = 16 + 9 = 25

m<LMN = 6x - 7 = 6(8) - 7 = 48 - 7 = 41

Answer:

m<OMN = 25

m<LMN = 41

User Carl Reid
by
4.3k points